Trolldomssak mot en samisk noaide - Anders Poulsen, Vadsø, 1692 - Willumsen, Liv Helene (Heimen, 2016)
Publisert versjon er også tilgjengelig hos utgiver: http://doi.org/10.18261/issn.1894-3195-2016-02-07